The Lead Coordination Polymers Containing Pyrazine-2,3-Dicarboxylic Acid: Rapid Structural Transformations and Cation Exchange - Wardana, F.Y.; Ng, S.W.; Wibowo, A.C. (American Chemical Society, 2015)
A new Pb-based coordination polymer synthesized with pyrazine-2,3-dicarboxylic acid (H2pzdc) is reported along with its structural characterizations. The compound, Pb2Cl2(Hpzdc)2(H2O)2 (1), is synthesized using a simple, aqueous-based dissolution-slow evaporation method with optimized conditions. It crystallizes in the C2/m space group (a = 11.561(1) Å, b = 8.4327(7) Å, c = 11.792(1) Å, β = 126.3070(8)°), with a 1D coordination polymer consisting of Pb2Cl2 dimers with monoprotonated dicarboxylic acids located between the chains. Soaking 1 in an aqueous solution of Hg(II) or Co(II) at room temperature resulted in a structural transformation into a newly formed 2D or 3D structure, respectively. The 2D compound, Pb(pzdc)(H2O) (2), crystallizes in the Pbca space group (a = 9.2624(9) Å, b = 12.0268(9) Å, c = 13.9430(8) Å), whereas the rapidly formed 3D compound, Pb2.67Co0.33(pzdc)3(H2O) (3), crystallizes in the P21/n space group (a = 10.9665(7) Å, b = 8.1909(4) Å, c = 25.0238(1) Å, β = 91.593(5)°). A structure similar to 3 without any dopant, Pb3(pzdc)3(H2O) (3a), is also synthesized. A rapid, room-temperature cation exchange is also observed when soaking 1 into an aqueous solution of Cu(II), giving a known structure. Systematic studies on the syntheses and characterizations of 1 and its remarkably rapid structural transformations and cation exchange at room temperature are presented.